Odoo-ERP as a Solution to Business Performance in Supply Chain of the Coffe Industry: A Systematic Literature Review - Mefid, Khairen Niza; Ahlunnazak, Ahmad Istiqlal (Fakultas Ekonomi Universitas Andalas, 2023)
Coffee is a highly valuable commodity that can be exported. The issue that arises is related to the supply chain, namely the suboptimal flow of goods within the supply chain. Hence, comprehending the notion of supply chain excellence is the initial step towards attaining a competitive edge in the supply chain. This paper is a literature review that analyzes prior research on the utilization of technology to enhance business operations through the implementation of enterprise resource planning (ERP) principles. This study employs the PRISMA approach. To resolve this issue, the recommended approach is to utilize OpenSource ERP software, specifically Odoo. Odoo is a software application that employs the concept of ERP to seamlessly integrate various business operations within a company. One of its key advantages is that it is available for free download and can be customized to suit the specific requirements of the firm. Odoo offers a comprehensive module that assists firms in several aspects of their operations, including CRM, Purchase Management, Accounting, Sales Management, and more. Through the utilization of the Odoo ERP system, firms may streamline and consolidate their operational procedures, resulting in a more organized and efficient performance while reducing potential risks. , , , ,